Analisis Pengelolaan Badan Usaha Milik Desa (BUMDES) dalam Perspektif Ekonomi Islam: Di Desa Rantau Badak Kabupaten Tanjung Jabung Barat - Ranti Khairunnisa; Usdeldi Usdeldi; G.W.I. Awal Habibah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This researcher aims to explain the management of BUMDES in Rantau Badak Village, West Tanjung Jabung Regency and the management of BUMDES from an Islamic economic perspective. This researcher uses a qualitative method, data collection techniques are obtained from observation, interviews and documentation related to this research. In this study, the researcher conducted interviews with the village head, the head of BUMDES and one of the people in Rantau Badak Village. Based on the results of the research that has been conducted by the researcher, it can be concluded that the types of businesses studied are two types of businesses, namely drinking water depots and tent rentals. Both types of businesses are managed by BUMDES Rantau Badak Village. In the management of BUMDES, it has been able to improve the community's economy, for example by opening up employment opportunities, training community skills and expertise, but the error lies in the lack of public awareness because they do not utilize the facilities available at BUMDES. Then the management of BUMDES from an Islamic economic perspective in Rantau Badak Village has moved towards sharia, namely in the tent rental business and drinking water depot business because it is ta'awun which means helping each other and which is not sharia, namely in Brilink because it contains usury, and BUMDES has moved towards sharia